Analisis Preferensi Konsumen Terhadap Pembelian Kopi Instan White Coffee Di Kecamatan Kebumen Kabupaten Kebumen - Jivana Zulfi; Kusnandar Kusnandar; Rr. Aulia Qonita (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
This research was aimed to determine the consumer preferences and attributes that most consumers consider in purchases of instant White Coffee in Kebumen Subdistrict Kebumen Regency. The basic method of this research is descriptive analytic by survey technique to the respondents directly. This research was conducted to respondents who had bought instant White Coffee with 96 respondents. The sampling technique was done with convenience sampling technique use questionnaires. Data analysis used is chi square operated by SPSS and fishbein multi attribute analysis. Based on the research results obtained the following conclusions: (1) consumer’s preference toward purchasing of instant white coffee purchase in Kebumen  Subdistrict  Kebumen  Regency  based  on  the  existing  attribute  is  flavor variant = original; promotion = purchase bonus; packaging = attractive appearance; and guarantee = halal; as well as the preferred product is Luwak White Koffie; and (2) The attributes of instant white coffee most considered in the purchase decision of instant white coffee in Kebumen Subdistrict Kebumen Regency are brand attributes.